2.0 users and new strategies for identifying information needs - Villaseñor Rodríguez, Isabel (2015)
This paper provides an approach from the Library and Documentation knowledge of the new user information "2.0 user", from the identification of its characteristic features from the study of its context consisting of determining the existence of a new culture, "culture 2.0" and belonging to a community. It also discusses some methodological techniques for study.